2015
DOI: 10.1590/0004-282x20150046
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pneumonia in acute stroke in patients in an emergency unit

Abstract: Objective To evaluate the risk factors and comorbid conditions associated with the development of pneumonia in patients with acute stroke. To determine the independent predictors of pneumonia. Method Retrospective study from July to December 2011. We reviewed all medical charts with diagnosis of stroke. Results 159 patients (18-90 years) were admitted. Prevalence of pneumonia was 32%. Pneumonia was more frequent in patients with hemorrhagic stroke (OR: 4.36; 95%CI: 1.9-10.01, p < 0.001), higher National Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
4
15
2
12
Order By: Relevance
“…Findings of the study showed that smoking, alcohol intake, dysphagia, age, hemorrhagic type of stroke, and need for intubation were factors independently increased the risk for developing pneumonia. Age, dysphagia, hemorrhagic stroke, and need for intubation have all been previously reported as risk factors for stroke-associated pneumonia, [1,4,5,[9][10][11][12][13] which is consistent with our findings. However, this study identified another risk factor not yet reported in literature which is alcohol intake, but the data on the amount and duration of alcohol intake were not obtained.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Findings of the study showed that smoking, alcohol intake, dysphagia, age, hemorrhagic type of stroke, and need for intubation were factors independently increased the risk for developing pneumonia. Age, dysphagia, hemorrhagic stroke, and need for intubation have all been previously reported as risk factors for stroke-associated pneumonia, [1,4,5,[9][10][11][12][13] which is consistent with our findings. However, this study identified another risk factor not yet reported in literature which is alcohol intake, but the data on the amount and duration of alcohol intake were not obtained.…”
Section: Discussionsupporting
confidence: 93%
“…Hemorrhagic stroke patients are more likely to develop pneumonia than those of ischemic stroke patients. [1] Furthermore, the need for intubation from respiratory failure is greater in hemorrhagic stroke (30% compared to 6% in ischemic stroke). [5] Dysphagia is a common complication of acute stroke, present in more than 50% of stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations